Untargeted Metabolomic Analysis of the Effects and Mechanism of Nuciferine Treatment on Rats With Nonalcoholic Fatty Liver Disease - Cui, Huantian; Li, Yuting; Cao, Min; Liao, Jiabao; Liu, Xiangguo; Miao, Jing; Fu, Hui; Song, Ruiwen; Wen, Weibo; Zhang, Zhaiyi; Wang, Hongwu (Frontiers in Pharmacology, 2020)
Metabolomic analysis has been used to characterize the effects and mechanisms of drugs for nonalcoholic fatty liver disease (NAFLD) at the metabolic level. Nuciferine is an active component derived from folium nelumbinis and has been demonstrated to have beneficial effects on a high-fat diet (HFD) induced hepatic steatosis model. However, the effect of the altered metabolites of nuciferine on NAFLD has not yet been elucidated. In this study, we established a NAFLD rat model using HFD and treated with nuciferine. The lipid content levels, pro-inflammatory cytokines, and oxidative stress were investigated to access the therapeutic effects of nuciferine. Additionally, the metabolic regulatory mechanisms of nuciferine on NAFLD were analyzed using untargeted metabolomics. Gene expression of the key enzymes related to the changed metabolic pathways following nuciferine intervention was also investigated. The results showed that nuciferine treatment significantly reduced the body weight, levels of lipids, and liver enzymes in the blood and improved the hepatic steatosis in the NAFLD rat model. Nuciferine treatment also increased the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and decreased the levels of methane dicarboxylic aldehyde (MDA) in the liver. Nuciferine treatment decreased the serum levels of interleukin (IL)-6, IL-1β, and tumor necrosis factor-alpha (TNF-α) and upregulated the gene expression of IL-6, IL-1β, and TNF-α in the liver. Metabolomic analysis indicated a metabolism disorder in the NAFLD rat model reflected in a dysfunction of the glycerophospholipid, linoleic acid, alpha-linolenic acid, arginine and proline metabolism. Conversely, treatment with nuciferine improved the metabolic disorder in the NAFLD rat model. Nuciferine treatment also regulated the gene expression of key enzymes related to the glycerophospholipid, linoleic acid, and alpha-linolenic acid metabolism pathways in the liver. In conclusion, our study demonstrated an amelioration of the metabolic disorders following nuciferine treatment in NAFLD rat model. Our study contributes to the understanding of the effects and mechanisms of drugs for complex diseases using metabolomic analysis and experimental approaches.